Prediction of measured GFR after living kidney donation from pre-donation parameters. Issue 1 (22nd June 2022) - van Londen, Marco; van der Weijden, Jessica; Niznik, Robert S; Mullan, Aidan F; Bakker, Stephan J L; Berger, Stefan P; Nolte, Ilja M; Sanders, Jan-Stephan F; Navis, Gerjan; Rule, Andrew D; de Borst, Martin H
ABSTRACT: Background: One of the challenges in living kidney donor screening is to estimate remaining kidney function after donation. Here we developed a new model to predict post-donation measured glomerular filtration rate (mGFR) from pre-donation serum creatinine, age and sex. Methods: In the prospective development cohort (TransplantLines, n = 511), several prediction models were constructed and tested for accuracy, precision and predictive capacity for short- and long-term post-donation 125 I-iothalamate mGFR. The model with optimal performance was further tested in specific high-risk subgroups (pre-donation eGFR <90 mL/min/1.73 m 2, a declining 5-year post-donation mGFR slope or age >65 years) and validated in internal ( n = 509) and external (Mayo Clinic, n = 1087) cohorts. Results: In the development cohort, pre-donation estimated GFR (eGFR) was 86 ± 14 mL/min/1.73 m 2 and post-donation mGFR was 64 ± 11 mL/min/1.73 m 2 . Donors with a pre-donation eGFR ≥90 mL/min/1.73 m 2 (present in 43%) had a mean post-donation mGFR of 69 ± 10 mL/min/1.73 m 2 and 5% of these donors reached an mGFR <55 mL/min/1.73 m 2 . A model using pre-donation serum creatinine, age and sex performed optimally, predicting mGFR with good accuracy (mean bias 2.56 mL/min/1.73 m 2, R 2 = 0.29, root mean square error = 11.61) and precision [bias interquartile range (IQR) 14 mL/min/1.73 m 2 ] in the external validation cohort. This model also performed well in donors with pre-donation eGFR <90 mL/min/1.73 m 2 [bias 0.35 mL/min/1.73 m 2 (IQR 10)], in donors with a negative post-donation mGFR slope [bias 4.75 mL/min/1.73 m 2 (IQR 13)] and in donors >65 years of age [bias 0.003 mL/min/1.73 m 2 (IQR 9)]. Conclusions: We developed a novel post-donation mGFR prediction model based on pre-donation serum creatinine, age and sex. Graphical Abstract: